Evaluating the efficacy of rBmHATαc as a multivalent vaccine against lymphatic filariasis in experimental animals and optimizing the adjuvant formulation - Dakshinamoorthy, Gajalakshmi (2013)
Developing an effective vaccine against lymphatic filariasis will complement the WHO's effort to eradicate the infection from endemic areas. Currently 83 different countries are endemic for this infection and over 1 billion people are at risk. An effective vaccine coupled with mass drug administration will reduce the morbidity and social stigma associated with this gruesome disease. Several potential vaccine candidates that can confer partial protection in experimental animals have been reported from different laboratories. However, no licensed vaccines are currently available for this disease. Among the several vaccine antigens identified from our laboratory, three most promising antigens; rBmHSPαc (α crystalline domain and c-terminal extension of Heat Shock Protein 12.6), rBmALT-2 (Abundant larval transcript) and rBmTSP LEL (Tetraspanin large extracellular loop) was further developed as a recombinant fusion protein vaccine (rBmHATαc). In a mouse model this fusion protein vaccine gave close to 68% protection following a challenge infection. To improve the vaccine efficiency of rBmHATαc, in this study we evaluated various preparations of alum (AL007, AL019, Alhydrogel and Imject® Alum) as adjuvants. Our results show that mice immunized with rBmHATαc formulated in AL007 (alum from IDRI) and/or AL019 (alum plus TLR-4 agonist from IDRI) gave the highest IgG antibody titer compared to other groups. Subsequent in vivo challenge experiments confirmed that >95% protection can be achieved when AL007 or AL019 was used as the adjuvant. However, when Imject® Alum or alhydrogel was used as the adjuvant only 76% and 72% protection respectively could be achieved. These results show that AL007 or AL019 (IDRI) is an excellent choice of adjuvant for the rBmHATαc vaccine against B. malayi L3 in mice.